Study on the mechanism of exogenous CaCl2 regulating cell growth and development to alleviate salt tolerance of alfalfa (Medicago sativa) - Liu, Huhu; Pan, Ling; Ahmad, Irshad; Bai, Yuyu; Shen, Sicong; Shi, Renhuang; Xu, Tingyang; Sun, Ying; Gao, Yang; Kang, Bowen; Lu, Yiwen; Wang, Xiaoshan (Frontiers in Plant Science, 2025)
Salt stress affects the growth and development of alfalfa. Calcium Chloride (CaCl2) plays a role in signal transduction and stabilizing cell membrane system in plant response to salt stress. However, the regulatory effect of CaCl2 on the growth and development of alfalfa cells under Sodium Chloride (NaCl) stress is not clear. This study analyzed the response and mitigation mechanism of adding 1mM CaCl2 to alfalfa seedlings under 120 mM NaCl stress. The results showed that the addition of CaCl2 increased the germination rate, vigor index and root length of alfalfa under salt stress. Secondly, the addition of CaCl2 reduced the activity of peroxidase, which led to the decrease of hydrogen peroxide (H2O2) and Malondialdehyde (MDA) content and catalase (CAT) activity. From the perspective of anatomical structure, the addition of CaCl2 under salt stress did not promote the elongation growth of alfalfa, which mainly reduced the area of root and leaf cells. Transcription sequencing showed that phenylpropanoid biosynthesis, Mitogen-Activated Protein Kinase (MAPK) signal transduction and photosynthesis pathways played a key role in alleviating NaCl stress when CaCl2 was added under salt stress. The up-regulation of genes including peroxidase (POD), chitinase (ChiB) and Light-Harvesting Complex (LHC) could regulate lignin accumulation and ethylene, abscisic acid and H2O2 transfer to defend against salt stress. In conclusion, CaCl2 can regulate the morphological physiology and antioxidant system of alfalfa, effectively alleviate the adverse effects of salt stress, and provide a basis for exploring the regulation of salt tolerance and the mitigation of salt stress